Serum Zinc Concentration and Helicobacter Pylori Serology in Hyperemesis Gravidarum - Evrim Erdemoğlu; Mehmet Güney; Tuğçe Çimen; Tamer Mungan (Gynecology Obstetrics & Reproductive Medicine, 2009)
OBJECTIVE: Plasma zinc levels and possible relationship with Helicobacter Pylori (HP) serology positivity in women with hyperemesis gravidarum (HEG) are studied in order to test hypothesis decreased zinc levels possibly induced by HP might have a pathogenic role in HEG. STUDY DESIGN: Thirty pregnant women with HEG and controls were enrolled into study. Zinc concentrations were determined by atomic absorption spectrophotometry. Specific serum antibodies directed against HP were measured. RESULTS: HP IgG antibodies were detected in 76.6% of HEG women and in 43.3% of controls (p<0.05). Mean of zinc level was 96.9±40.1 micromol/l and 80.9±16.6 micromol/l in HEG and controls, respectively (p>0.05). Zinc levels were not correlated either with helicobacter pylori serology or study groups (p>0.05). CONCLUSION: Serum zinc level is not altered by HEG and HP infection. There might be a possible association between HEG and HP, however there was no relation between HEG, HP and zinc.